Lifetime Improvement of Contact Brush Units of Automotive Power Machines. Part 2 - Dovhal, A.H.; Biliakovych, O.M.; Pryimak, L.B. (Problems of Tribology, 2026)
Lifetime testing of contact brush units of automotive power machines is held. Friction contact of copper and graphite under working voltage and current within ordinary atmosphere environment was simulated on the friction test bench. Wear resistance and friction losses have been detected. Wear mechanisms and friction surfaces were investigated using the scanning electronic microscopy. This study allows recommendation the optimal surface treatment of copper elements of contact brush unit of alternators or commutator unit of power starters.